EXPERIENCES OF GRANDMOTHERS LOOKING AFTER GRANDCHILDREN EXHIBITING DELINQUENT BEHAVIOURS IN HILL CREST LOCATION, ALICE TOWNSHIP, EASTERN CAPE: IMPLICATIONS FOR SOCIAL WORK - Kang’ethe, Simon; Mugedya, Samuel; Nomngcoyiya, Thanduxolo (Social Work/Maatskaplike Werk, 2022)
Older persons face an array of challenges with regard to parenting a delinquent grandchild. The study adopted a qualitative approach with the use of an explorative and descriptive design, with data collected from in-depth interviews with grandparents, communities and probation officers. The study also adopted phenomenology as the specific research approach. Findings revealed that grandparents parenting their grandchildren face the pernicious experiences of grandchildren’s delinquency; financial challenges and poverty; and deterioration of their health and social life. This paper recommends that the government prioritise the grandparents’ vulnerability to address the delinquency of their grandchildren and ensure that they are freed from such a pernicious preoccupation. Policies should be developed to ensure that grandparents above the age of 60 years should not assume full custody of children, as they are also a vulnerable population.